Influence of Ch substitution on structural, electronic, and thermoelectric properties of layered oxychalcogenides (La0.5Bi0.5O)CuCh (Ch = S, Se, Te): a new insight from first principles. Issue 46 (22nd July 2020) - Muhammady, Shibghatullah; Widita, Rena; Darma, Yudi
Abstract : Substituting Ch from S to Se to Te enhances local-symmetry distortion and thermoelectricity of (La0.5 Bi0.5 O)CuCh from first principles. Abstract : We study the structural, electronic, and thermoelectric properties of p-type layered oxychalcogenides (La0.5 Bi0.5 O)CuCh (Ch = S, Se, Te) from first principles. Ch substitution from S to Te enhances the local-symmetry distortions (LSDs) in CuCh4 and OLa2 Bi2 tetrahedra, where the LSD in OLa2 Bi2 is more pronounced. The LSD in CuCh4 tetrahedra comes from the possible pseudo-Jahn–Teller effect, indicated by the degeneracy-lifted t2g and eg states of Cu 3d 10 orbital. The Ch substitution decreases bandgap from 0.529, 0.256 (Γ → 0.4Δ), to 0.094 eV (Z → 0.4Δ), for Ch = S, Se, Te, respectively, implying the increasing carrier concentration and electrical conductivity. The split-off energy at Z and Γ points are also increased by the substitution. The valence band shows deep O 2p states in the electron-confining [LaBiO2 ] 2+ layers, which is essential for thermoelectricity. (La0.5 Bi0.5 O)CuTe provides the largest thermoelectric power from the Seebeck coefficient and the carriers concentration, which mainly come from Te 5p x /p y, Cu 3d zx, and Cu 3d zy states. The valence band shows the partial hybridization of t2g and Chp states, implied by the presence of nonbonding valence t2g states. This study provides new insights, which predict experimental results and are essential for novel functional device applications.